"HLA‐10‐SNP": A new qPCR‐based system for rapid, effective, and accurate detection of 10 important SNPs in the HLA region. (9th September 2021) - Zheng, Zhong‐Zheng; Li, Dai‐Yang; Du, Ke‐Ming; Xu, Xiang; Wang, Ning‐Juan; Yuan, Zhi‐Yang; Li, Bo‐An
Abstract : Mastering the SNP content in the HLA region can be based on it to judiciously select unrelated donor stem cells with preferable MHC matching to lower postoperative complications. Herein, quantitative PCR‐based primers and probes were designed for 10 transplants outcome‐associated SNP loci with two‐allelic polymorphism, and then a new detection system ("HLA‐10‐SNP") was established. Compared with Sanger sequencing, its accuracy has been proven to reach 100%. Additionally, fluorescent PCR typing of 10 important SNPs via this system expressed excellent repeatability (sensitivity, 20 ng). Overall, the new system achieves single‐sample classification precision and easily distinguishable results, equipped with the advantages of simple, rapid, accurate, and effective, promising to acquire widespread popularization and application in clinical settings.